A note about administration and Cryptography: The case of complexity and administration (2010)
This text argues in favor of coordinated work between the sciences of complexity and administration, particularly when it involves problems of information and security. Cryptography must therefore be seen as both a field that must be incorporated within the body of studies on administration in general as well as a case study for the durability of organizations. The touchstone is therefore the relationship between complexity and strategy.